Heavenly bodies : fashion and the Catholic imagination - Bolton, Andrew, 1966-; Boehm, Barbara Drake; Cataldi Gallo, Marzia; Mann, C. Griffith; Morgan, David, 1957-; Ravasi, Gianfranco; Tracy, David; Jebb, Katerina, 1962-; Metropolitan Museum of Art (New York, N.Y.) (New York : The Metropolitan Museum of Art, 2018)
A brilliant exploration of fashion's complex engagement with the great art and artifacts of Catholic faith and practice Since antiquity, religious beliefs and practices have inspired many of the masterworks of art. These works of art have, in turn, fueled the imagination of fashion designers in the 20th and 21st centuries, yielding some of the most innovative creations in costume history. Connecting significant religious art and artifacts to their sartorial expressions, Heavenly Bodies: Fashion and the Catholic Imagination provides a critical analysis of fashion's engagement with notions of the divine. Exploring fashion's complex and often controversial relationship with Catholicism, Heavenly Bodies probes what dress reveals about the state of religion and spirituality within contemporary culture, and how it may manifest-or subvert-Catholic values and ideology. Art objects, such as devotional paintings and altarpieces from The Met's collection, are presented alongside fashions from designers including Cristobal Balenciaga, Callot Soeurs, Domenico Dolce and Stefano Gabbana, John Galliano, Jean-Paul Gaultier, Madame Gres, Christian Lacroix, Karl Lagerfeld, Jeanne Lanvin, Claire McCardell, Alexander McQueen, Thierry Mugler, Elsa Schiaparelli, and Gianni Versace. The volume also presents a selection of ecclesiastical vestments and accessories from the Vatican collection, many of which have not been published before.
Volume [1]. I. The Vatican collection -- Volume [2]. II. Fashioning worship; III. Fashioning devotion.
Catalog of an exhibition at The Metropolitan Museum of Art, New York, May 10-October 8, 2018.
Issued in a slip case.
Includes bibliographical references (page 330).
Keywords: Metropolitan Museum of Art (New York, N.Y.) -- Catalogs; 1900-2099; Church vestments -- Catholic Churvch -- Exhibitions; Christian art and symbolism -- Influence -- Exhibitions; Fashion -- History -- 20th century -- Exhibitions; Fashion -- History -- 21st century -- Exhibitions; Fashion design -- History -- 20th century -- Exhibitions; Fashion design -- History -- 21st century -- Exhibitions; Church vestments -- Vatican City -- Exhibitions; Christian art and symbolism -- Influence; Church vestments; Fashion; Fashion design; Kleidung; Mode; Vatican City; Exhibition catalogues; Exhibition catalogs; History; Exhibition catalogs